Menghadapi Satu Dekade Implementasi Tujuan Pembangunan Berkelanjutan: Pemetaan Tren Menggunakan Analisis Bibliometrik - Junita Praja, Selvia; Sartika, Ika; Alma'arif, Alma'arif (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
Sustainable Development Goals (SDGs) are a global agenda designed to achieve the welfare of the world community until 2030. This study aims to analyze the trend of research publications on SDGs with a bibliometric analysis approach. The articles used in this study were obtained from Scopus data. From 352 articles found in the Scopus database between 2018 and 2024, the data cleaning process used open refine. The selected articles were then managed using Biblioshiny and VOSviewer software. The results showed that publications related to SDGs experienced fluctuations from 2018 to 2024. and also experienced an increasing trend in 2024. The article with the most citations, entitled Global, regional, and National Causes of under-5 Mortality in 2000-19: An Updated Systematic Analysis with Implications for the Sustainable Development Goals, has the most citations of 566 citations. Meanwhile, the highest affiliation shows that the University of Washington is the institution with a total of 81 publications. Mapping articles based on the relationship between keywords (co-occurrence) is formed into 4 clusters; based on the publication history of sustainable development, humans and women are the topics that are most often the focus of discussion. Meanwhile, potential topics that can be further developed include the Sustainable Development Goals (SDGs)